CompNanoTox2015: novel perspectives from a European conference on computational nanotoxicology on predictive nanotoxicology. Issue 7 (9th August 2017) - Bañares, Miguel A.; Haase, Andrea; Tran, Lang; Lobaskin, Vladimir; Oberdörster, Günter; Rallo, Robert; Leszczynski, Jerzy; Hoet, Peter; Korenstein, Rafi; Hardy, Barry; Puzyn, Tomasz
Abstract: A first European Conference on Computational Nanotoxicology, CompNanoTox, was held in November 2015 in Benahavís, Spain with the objectives to disseminate and integrate results from the European modeling and database projects (NanoPUZZLES, ModENPTox, PreNanoTox, MembraneNanoPart, MODERN, eNanoMapper and EU COST TD1204 MODENA) as well as to create synergies within the European NanoSafety Cluster. This conference was supported by the COST Action TD1204 MODENA on developing computational methods for toxicological risk assessment of engineered nanoparticles and provided a unique opportunity for cross fertilization among complementary disciplines. The efforts to develop and validate computational models crucially depend on high quality experimental data and relevant assays which will be the basis to identify relevant descriptors. The ambitious overarching goal of this conference was to promote predictive nanotoxicology, which can only be achieved by a close collaboration between the computational scientists (e.g. database experts, modeling experts for structure, (eco) toxicological effects, performance and interaction of nanomaterials) and experimentalists from different areas (in particular toxicologists, biologists, chemists and material scientists, among others). The main outcome and new perspectives of this conference are summarized here.